Properties of the series of exponents whose indices have finite density - Krutigolova , E. K. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
Conditions are presented for the summability by the Abel method of exponential series with complex exponents, having finite angular density at the noncorner points of the boundary of the convex polygonal domain of convergence of the series; conditions are established for the convergence of these series at the points indicated above.